The Constitutional Adjudication in Indonesia: Bridging Political Legitimacy and the Supremacy of Law - Pratama, Topan Yulia; Virdaus, Saivol; Kurniawan, Dimas Tri (JURNAL LEGALITAS, 2025)
Judicial review in Indonesia occupies a strategic position as a guardian of constitutional supremacy and an arena for tensions between the principles of the rule of law and popular sovereignty. This article aims to assess the effectiveness of judicial review in protecting citizens' constitutional rights and unravel the challenges of independence, public access, and compliance with decisions. Using a juridical-normative method through statutory, case, and conceptual approaches, the study describes norms, interprets constitutional provisions, and evaluates the practice of constitutional justice. The findings reveal three key issues: first, the vulnerability of independence due to recruitment processes that overlap with political interests and lead to inconsistent reasoning; second, barriers to access in the form of strict legal standing requirements, procedural complexity, costs, and low legal literacy; and third, weak implementation of decisions that give rise to "constitutional non-compliance," eroding the coercive power of judicial review and creating legal uncertainty. Although there are progressive decisions that expand rights protection, their implementation impact is often diminished by institutional resistance. This article recommends reforms to more independent and transparent judicial selection, expanding access through constitutional legal aid and simplifying procedures, and strengthening monitoring mechanisms and sanctions for the implementation of decisions. Synergy of these steps is necessary so that judicial review truly becomes an effective instrument for enforcing the constitution and supporting people's sovereignty.